If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X * x) + ((3x)(3x)) = (24 * 24) Multiply X * x (xX) + ((3x)(3x)) = (24 * 24) xX + ((3x)(3x)) = (24 * 24) Remove parenthesis around (3x) xX + (3x(3x)) = (24 * 24) Remove parenthesis around (3x) xX + (3x * 3x) = (24 * 24) Reorder the terms for easier multiplication: xX + (3 * 3x * x) = (24 * 24) Multiply 3 * 3 xX + (9x * x) = (24 * 24) Multiply x * x xX + (9x2) = (24 * 24) Multiply 24 * 24 xX + (9x2) = (576) xX + (9x2) = 576 Solving xX + (9x2) = 576 Solving for variable 'x'. Reorder the terms: -576 + xX + (9x2) = 576 + -576 Combine like terms: 576 + -576 = 0 -576 + xX + (9x2) = 0 The solution to this equation could not be determined.
| 10b-9b+7b+3b+1=45 | | 45h+11=34h+55 | | 12a-11a-a+11a+3=36 | | 7×1/2= | | (X-3)(x^2+4x+19)=0 | | 5g+6k=g | | 10x+5=2x-8x | | 15x^5-5/5x^4-10 | | 9q-5q+4q-6q-2=14 | | -4x^2-32x-48=0 | | (-3x-4y)(9x^2-12xy+16y^2)= | | I=1000-40(7) | | -2(3x+5)-2x=x-43 | | -4/11x=8/99 | | 2.25x+5=13.5t+14 | | 252=(4+y)16.8 | | 4(x+2)=4(x+13) | | -8x+36= | | n+n+2+n+4=-78 | | 44t+t-49t-t+6t=6 | | 5x-70=3x-90 | | 54=1/6w | | -6=d/3 | | Y=-7/3x-4 | | 1/6w=54 | | 9.3=31n | | 1+2=2+7 | | 0=2x^4-4x^2-48 | | X=7/3y-4 | | 3a+21=4a-60 | | 23n+5n-24n-4n+10n-3=17 | | I=1000-40r |